Integrated approach for effective bioethanol production using whole slurry from autohydrolyzed Eucalyptus globulus wood at high-solid loadings - Romaní, Aloia (2014)
One of the most important targets and challenges in the second generation bioethanol is the development of a cost-effective process on large-scale. In this context, the high solid loading on saccharification and fermentation and the use of whole-slurry from pretreatment could be promising alternatives to obtain high ethanol concentrations and to decrease operational costs and wastewater. In this work, Eucalyptus globulus wood was submitted to non-isothermal autohydrolysis treatment (Tmax = 210 °C) and the whole-slurry obtained was assayed for the optimization of enzymatic saccharification at different solid and enzymes (CTec2 and HTec2) loadings using a Box–Behnken experimental design. Under the optimized conditions (liquid solid ratio 6.4 g/g, cellulase to substrate ratio 22.5 FPU/g and hemicellulase to substrate ratio 500 UI/g), two strategies were evaluated for ethanol production (Simultaneous Saccharification and Fermentation, SSF and Presaccharification and Simultaneous Saccharification and Fermentation, PSSF), using an industrial and robust Saccharomyces cerevisiae strain. High concentrations of ethanol (50.2 and 48.8 g/L) and productivities (0.63 and 0.55 g/L h) were obtained by SSF and PSSF, respectively. The SSF process proved to be an advantageous strategy to obtain concentrations >6% (v/v) of ethanol with elevated conversion (95%) even employing high solid loading and non-detoxified hydrolysate. Following an integrated optimization process, cost-effective bioethanol production conditions from whole-slurry E. globulus wood were determined and validated experimentally, representing a step-forward towards its industrial implementation.